FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI DAN DAMPAKNYA TERHADAP KEBERHASILAN USAHA KECIL DI KABUPATEN BANYUMAS - Umi Pratiwi; Bambang Setyubudi Irianto (Universitas Semarang, 2020)
The aims of this research is (1) to test impacts of bussiness scale, education grade,firm's age, and accounting training on use accounting information of Small enterprises in Banyumas; (2) to test impact of use accounting information on performance of Small enterprises in Banyumas.Data used in this research collected with questionaire from 77 respondents. Data analyzed using multiple linear regression. The result show that partially, business scale, education grade and accounting training have impact the use accounting information significantly. Furthermore firm's age have no effect significantly to the use accounting information significantly of the in Sokaraja, Banyumas. Then result show that accounting information have impactt to performance small enterprisessignificantlyKeyword : bussiness scale, eduction grade, firm's age, and accounting training, to use accounting iriformation,performance small enterprise